(untitled) (Journal of the College of Basic Education, 2022)
This study examines Language Learning Strategies and their relation with language. Language Learning Strategies is considered one of the studies important for foreign students. Explain the concept of learning strategies and communication in the context of an explanatory model based on the cognitive mediation